Tiny Pd@Co Core–Shell Nanoparticles Confined inside a Metal–Organic Framework for Highly Efficient Catalysis. Issue 1 (8th September 2014) - Chen, Yu‐Zhen; Xu, Qiang; Yu, Shu‐Hong; Jiang, Hai‐Long
<x xml:space="preserve">Abstract</x> A new strategy to pre‐incorporate metal precursors followed by their in situ reduction is established to prepare tiny core–shell nanoparticles (NPs) stabilized by a metal–organic framework (MOF). The obtained Pd@Co core–shell NPs of ∼2.5 nm confined in the pores of a mesoporous MOF, MIL‐101, exhibit synergistic and superior catalytic performance in hydrolytic dehydrogenation of NH3BH3 under mild conditions compared to their monometallic and alloy counterparts as well as Pd@Co NPs located on a MOF surface. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>